Treatment of implant surfaces: Insights, outcomes and limitations - Corrêa, Càssia Bellotto; Ribeiro, Ana Lucia Roselino; Moretti, Livia Alves Corrêa [UNESP]; Consolaro, Alberto; Junior, Elcio Marcantonio [UNESP] (My University, 2015)
Enhancements in the microstructure and nanostructure of implant surfaces have been performed in order to increase the quality and quantity of bone-implant contact during the osseointegration process. The purpose of this chapter was to investigate the implant surfaces cited in the literature and/or commercially available, as well as its effects on the process of osseointegration and also discuss the influence of the implant surface on the bacterial adhesion. Nowadays, a variety of titanium implants surface treatments can be found on the market or are under analysis, including machined dental implants, sandblasting, acidetching, laser ablation, plasma-spray titanium technique, plasma-spray hydroxyapatite technique, sol-gel, anodization, biomimetic coating with calcium phosphates and surfaces with incorporation of drugs. The modification of implant surfaces directly influences bacterial adhesion which in turn, is closely related to the development of peri-implantitis and lack of osseointegration.